ProBNP for stratifying patients with heart failure - Pereira-Barretto,Antonio Carlos (2003)
OBJECTIVE: To verify whether the serum levels of N-Terminal ProBNP fraction (ProBNP) allow us to identify with accuracy the clinical functional status of patients with heart failure (HF), because the clinical diagnosis of this syndrome is based basically on clinical data when the complementary tests have lower specificity. METHODS: Sixty-nine patients with a history of HF were studied. Their mean age of was 53.5 years and 78.3% were males. All underwent clinical and echocardiographic evaluations and a test to determine the serum dosage of ProBNP. According to clinical manifestation, patients were in the following functional classes (FC), 14% FC I, 40.6% FC II, 28.1% FC III, and 23.4% FC IV. The mean ejection fraction (EF) was 0.28. RESULTS: ProBNP did not differ according to age, sex, and cause of cardiopathy. No correlation existed between EF and the ProBNP serum level. ProBNP levels were significantly lower in patients in FC I than those in FC II (42 vs 326.7 pmol/L; P=0.0001), and in FC II than those in FC III (P=0.01). ProBNP levels did not differ statically between FC III and IV patients (888.1 vs 1082.8 pmol/L; P=0.25). ProBNP values greater than 100 pmol/L identify patients with decompensated HF with a sensitivity of 98%. CONCLUSION: ProBNP values over 100 pmol/L were indicative of HF, and patients with advanced HF had values over 270 pmol/L. A ProBNP dosage test was an excellent auxiliary in the clinical characterization of patients with HF.